NF1 mutations are recurrent in adult acute myeloid leukemia and confer poor outcome - Eisfeld, Ann-Kathrin (Leukemia, 2018)
Targeted mutation assessment of 81 genes in 1,021 adults with de novo acute myeloid leukemia (AML) identified recurrent mutations in the neurofibromin 1 (NF1) gene in 52 (5.1%) patients, including 36 (5.2%) younger and 16 (4.8%) older patients, which suggests NF1 belongs to the 20 most frequently mutated genes in adult AML. NF1 mutations were found throughout the gene, and comprised missense, frame-shift and nonsense mutations. One mutation hotspot, at amino acid threonine 676 (Thr676), was found in 27% of AML patients with NF1 mutations. NF1-mutated patients belonged more often to the adverse European LeukemiaNet (ELN) risk category than NF1 wild-type patients. Among patients aged <60 years, the presence of NF1 Thr676 mutations was associated with lower complete remission (CR) rates (P=0.04) and shorter overall survival (OS; P=0.01), as was the presence of any NF1 mutation in patients in the adverse ELN risk category (CR, P=0.05; OS, P<0.001). CR rates were also lower in NF1-mutated patients aged ≥60 years compared with NF1 wild-type patients (P=0.001). In summary, our findings provide novel insights into the frequency of NF1 mutations in AML, and are suggestive of an adverse prognostic impact in patients treated with standard chemotherapy.